A Long‐Cycling Aqueous Zinc‐Ion Pouch Cell: NASICON‐Type Material and Surface Modification. Issue 9 (30th March 2020) - Zhang, Xianghua; Chen, Haoliang; Liu, Weiling; Xiao, Ni; Zhang, Qi; Rui, Xianhong; Huang, Shaoming
Abstract: Aqueous zinc‐ion batteries (ZIBs) have become the highest potential energy storage system for large‐scale applications owing to the high specific capacity, good safety and low cost. In this work, a NASICON‐type Na3 V2 (PO4 )3 cathode modified by a uniform carbon layer (NVP/C) has been synthesized via a facile solid‐state method and exhibited significantly improved electrochemical performance when working in an aqueous ZIB. Specifically, the NVP/C cathode shows an excellent rate capacity (e. g., 48 mAh g −1 at 1.0 A g −1 ). Good cycle stability is also achieved (e. g., showing a capacity retention of 88% after 2000 cycles at 1.0 A g −1 ). Furthermore, the Zn 2+ (de)intercalation mechanism in the NVP cathode has been determined by various ex‐situ techniques. In addition, a Zn||NVP/C pouch cell has been assembled, delivering a high capacity of 89 mAhg −1 at 0.2 A g −1 and exhibiting a superior long cycling stability. Abstract : A long‐cycling aqueous zinc‐ion pouch cell is reported by using the cathode material of the surface‐protected (a uniform carbon layer) NASICON‐type Na3 V2 (PO4 )3 (NVP/C). Furthermore, the zinc storage mechanism has been systematically investigated. The NVP/C is fabricated by a facile solid‐state reaction, which is suitable for large‐scale applications.